Lithium complex oxide

By adjusting the chemical composition and particle structure of lithium composite oxides, it ensures that it maintains a certain (104) peak wide range in XRD analysis, and forms a dual-mode structure by mixing large and small particles, solving the problem of degradation of battery life characteristics caused by the structural instability of nickel-rich positive electrode active materials, and achieving battery performance with high battery capacity and long life.

JP2025069301AActive Publication Date: 2025-04-30ECOPRO BM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025015135
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-31
Filing Date
2025-01-31
Publication Date
2025-04-30
Estimated Expiration
2040-10-29

AI Technical Summary

Technical Problem

In the prior art, when the nickel-rich positive electrode active material increases structural instability, resulting in a decrease in battery life characteristics.

Method used

By adjusting the chemical composition and particle structure of the lithium composite oxide, it ensures that it maintains a certain (104) peak width (FWHM) range in XRD analysis, and forms a dual-mode structure by mixing large and small particles to stabilize the nickel content and the electrochemical performance of the battery.

Benefits of technology

It is achieved to improve the battery life characteristics of nickel-rich positive electrode active materials while maintaining high battery capacity, and avoid degradation of battery performance due to structural instability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069301000001_ABST
    Figure 2025069301000001_ABST
Patent Text Reader

Abstract

To provide a lithium complex oxide improved in terms of life characteristics and capacity characteristics by maintaining a predetermined relationship with a mole fraction of nickel in an active material and a mass ratio between first particles and second particles and controlling a full width at half maximum value in XRD measurement to be within a predetermined range.SOLUTION: A lithium complex oxide includes a mixture of first particles of n1 (n1>40) aggregated primary particles and second particles of n2 (n2≤20) aggregated primary particles, and is represented by the composition shown in the following formula: LiaNixCoyMnzM1-x-y-zO2, wherein M is selected from: B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, 0.9≤a≤1.3, 0.6≤x≤1.0, 0.0≤y≤0.4, 0.0≤z≤0.4, and 0.0≤1-x-y-z≤0.4.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mixture of lithium composite oxides, and more specifically, to a lithium composite oxide in which, when first particles and second particles having different numbers of aggregates of primary particles are mixed, a certain relationship is maintained between the range of the full width at half maximum (FWHM) value of the (104) peak of XRD defined by a hexagonal lattice having an R-3m space group, the mole fraction of nickel in the lithium composite oxide, and the mass ratio of the first particles to the second particles, thereby resulting in an effect of improving the life characteristics of a battery containing the lithium composite oxide according to the present invention. [Background technology]

[0002] As various devices become smaller and more powerful, importance is being placed on lithium batteries that are not only smaller and lighter, but also have higher energy density, i.e., lithium batteries with high voltage and high capacity are becoming more and more important.

[0003] Lithium composite oxides used as positive electrode active materials in lithium batteries include, for example, LiCoO 2 , LiMn 2 O 4 , LiNiO 2 , LiMnO 2 Among the lithium composite oxides, LiCoO 2 is the most widely used due to its excellent life characteristics and charge / discharge efficiency, but it has disadvantages in that it is poor in structural stability and expensive due to the limited availability of cobalt resources used as a raw material, limiting its competitiveness.

[0004] LiMnO 2 , LiMn 2 O 4 Lithium manganese oxides such as those mentioned above have the advantages of being excellent in thermal stability and low in cost, but have the disadvantages of being low in capacity and poor in high-temperature properties.

[0005] In addition, LiNiO 2 Although the positive electrode active material based on this system shows battery characteristics such as high discharge capacity, the synthesis is difficult due to the problem of cation mixing between Li and transition metals, which causes a serious problem in the rate characteristics.

[0006] To make up for these shortcomings, the demand for nickel-rich systems with Ni content of 60% or more as the positive electrode active material for secondary batteries has started to increase. However, while the above-mentioned nickel-rich system active material has the excellent advantage of exhibiting high capacity, there are problems with rapid deterioration of life characteristics at room temperature and high temperature due to increased structural instability caused by Li / Ni cation mixing, physical disconnection between internal particles due to microcracks, and deepening electrolyte depletion as the Ni content increases. Summary of the Invention [Problem to be solved by the invention]

[0007] The occurrence of microcracks, which is known to be a cause of deterioration in the lifespan of nickel-rich positive electrode active materials, is said to be correlated with the size of the primary particles of the positive electrode active material. Specifically, it is known that the smaller the size of the primary particles, the more the occurrence of cracks due to repeated particle contraction / expansion is suppressed. However, there is a problem that the discharge capacity decreases when the size of the primary particles decreases, and when the nickel content in the positive electrode active material increases, the life characteristics may deteriorate if the size of the primary particles decreases. Therefore, in order to improve the life characteristics of nickel-rich positive electrode active materials, it is necessary to consider the correlation between the nickel content, the size of the primary particles, and the discharge capacity.

[0008] In order to solve the problems of the nickel-rich lithium composite oxide described above, the present invention aims to provide a lithium composite oxide having improved life characteristics and capacity characteristics by adjusting the full width at half maximum (FWHM) value within a predetermined range during XRD measurement so that a certain relationship is maintained between the mole fraction of nickel in the active material and the mass ratio of the first particles to the second particles. [Means for solving the problem]

[0009] In order to solve the above problems, the lithium composite oxide according to the embodiment of the present invention includes a mixture of first particles in which n1 (n1>40) primary particles are aggregated, and second particles in which n2 (n2≦20) primary particles are aggregated, and is represented by the following [Chemical Formula 1]. The range of the full width at half maximum (FWHM) (deg., 2θ) of the (104) peak in the XRD peak defined by a hexagonal lattice having an R-3m space group is represented by the following [Relational Formula 1].

[0010] [Chemical formula 1] Li a Ni x Co y Mn z M 1-x-y-z O 2 (In the formula, M is selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and 0.9≦a≦1.3, 0.6≦x≦1.0, 0.0≦y≦0.4, 0.0≦z≦0.4, and 0.0≦1-xyz≦0.4.)

[0011] [Equation 1] -0.025≦FWHM (104) -{0.04+(x 第1の粒子 -0.6) × 0.25}≦0.025 (In the formula, FWHM (104) is expressed as follows in [Equation 2]:

[0012] [Equation 2] FWHM (104) ={(FWHM 化学式1のpowder(104)-0.1 × mass ratio of second particle) / mass ratio of first particle}-FWHM Si powder(220) (In the formula, FWHM 化学式1のpowder(104) indicates the full width at half maximum (FWHM) of the (104) peak observed at about 44.5° (2θ) from the XRD measurement of the lithium composite oxide. Si powder(220) indicates the full width at half maximum (FWHM) of the (220) peak observed at about 47.3° (2θ) from the XRD measurement of Si powder. 第1の粒子 =(xx 第2の粒子 * mass ratio of the second particle) / mass ratio of the first particle, 第2の粒子 means the Ni molar ratio of the second particles. The mass ratio means the ratio of the mass to the total mass of the first particles and the second particles combined.)

[0013] If particles having more than n1 primary particles distinguishable by the naked eye in SEM analysis are defined as "multiple particles" and particles having n2 or less primary particles are defined as "single particles," the lithium composite oxide according to the embodiment of the present invention has a bimodal structure of mixed single particles in which large particles in the form of multiple particles and small particles in the form of single particles are mixed.

[0014] When a positive electrode active material having a bimodal structure with mixed single particles is applied to a secondary battery, the BET is reduced, gas generation is suppressed, and storage characteristics are improved compared to the case of using a bimodal positive electrode active material with mixed multiparticles in which large particles in a multiparticle form are mixed with small particles in a multiparticle form.

[0015] The secondary particles of the lithium composite oxide according to the embodiment of the present invention may have 20 or less, 15 or less, 10 or less, or 5 or less primary particles.

[0016] In the lithium composite oxide according to the embodiment of the present invention, as shown in the above [Relation 1], the range of the half-width FWHM of the (104) peak in the XRD analysis is the nickel content (x 第1の粒子), and the mass ratio of the first particles to the second particles.

[0017] According to the [Relation 1], the optimal range of FWHM of the lithium composite oxide according to the embodiment of the present invention may be −0.25 to 0.25, or −0.20 to 0.20. When the lithium composite oxide having a bimodal structure of mixed single particles within the optimal range of FWHM is applied to a secondary battery, excellent battery storage characteristics can be obtained.

[0018] In the lithium composite oxide according to the embodiment of the present invention, during XRD analysis, the full width at half maximum (FWHM) value is subject to deviation and error due to various variable factors such as the condition of the analysis device, the X-ray source, and the measurement conditions. Therefore, as shown in the above [Relation 2], the full width at half maximum (FWHM) of Si powder as a standard sample is used for correction.

[0019] In the lithium composite oxide according to the embodiment of the present invention, the average particle size of the first particles may be 8 to 20 μm, 9 to 18 μm, 10 to 15 μm, or 10 to 13 μm.

[0020] In the lithium composite oxide according to the embodiment of the present invention, the average particle size of the second particles may be 0.1 to 7 μm, 2 to 5 μm, or 3 to 4 μm.

[0021] The crystal structure of the lithium composite oxide according to the embodiment of the present invention is a hexagonal α-NaFeO 2 (R-3m space group).

[0022] In the lithium composite oxide according to the present invention, when the nickel content x in the [chemical formula 1] is 0.97 to 0.99, the FWHM represented by the [relationship formula 2] (104) The range can be 0.108° (2θ) to 0.162° (2θ).

[0023] In the lithium composite oxide according to the present invention, when the nickel content x in the [chemical formula 1] is 0.93 to 0.95, the FWHM represented by the [relationship formula 2] (104) The range can be 0.098° (2θ) to 0.152° (2θ).

[0024] In the lithium composite oxide according to the present invention, when the nickel content x in the [chemical formula 1] is 0.87 to 0.89, the FWHM represented by the [relationship formula 2] (104) The range can be 0.083° (2θ) to 0.137° (2θ).

[0025] In the lithium composite oxide according to the present invention, when the nickel content x in the [chemical formula 1] is 0.79 to 0.81, the FWHM represented by the [relationship formula 2] (104) The range can be 0.063° (2θ) to 0.117° (2θ).

[0026] Although not specifically described in the present invention, various peaks such as (003) and (101) are observed in addition to the (104) peak during XRD analysis of the lithium composite oxide according to the present invention, and each peak has a different FWHM value. Similarly, peaks detected from different positions in addition to the (104) peak during XRD analysis of the lithium composite oxide according to the present invention may have different FWHM ranges that maintain a certain relationship with the mole fraction of nickel and the mass ratio of the first particles to the second particles.

[0027] A method for producing a lithium composite oxide according to an embodiment of the present invention includes a first step of synthesizing a first cathode active material precursor including first particles formed by agglomerating n1 (n1>40) primary particles, adding a lithium compound, and calcining the resulting material to produce a first cathode active material; a second step of synthesizing a second cathode active material precursor including second particles formed by agglomerating n2 (n2≦20) primary particles, adding a lithium compound, and calcining the resulting material; a third step of pulverizing the material formed in the second step to produce a second cathode active material; a fourth step of mixing the first cathode active material and the second cathode active material; and a fifth step of coating or doping the mixed material with a substance M, followed by heat treatment.

[0028] In the method for producing a lithium composite oxide according to the embodiment of the present invention, the lithium compound added in the first step and the second step may be LiOH.

[0029] In the method for producing a lithium composite oxide according to the embodiment of the present invention, the average particle size of the first positive electrode active material produced in the first step can be 8 to 20 μm, 9 to 18 μm, 10 to 15 μm, or 10 to 13 μm.

[0030] In the method for producing a lithium composite oxide according to the embodiment of the present invention, the second positive electrode active material produced in the third step may have an average particle size of 0.1 to 7 μm, 2 to 5 μm, or 3 to 4 μm.

[0031] In the method for producing a lithium composite oxide according to the embodiment of the present invention, a step of washing with water may be further included after the calcination in the first step, after the calcination in the second step, or after the pulverization in the third step.

[0032] In the method for producing a lithium composite oxide according to the embodiment of the present invention, a step of washing with water may be further included after the heat treatment in the fifth step.

[0033] In the method for producing a lithium composite oxide according to the embodiment of the present invention, in the fifth step, the substance M is selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, but is not limited thereto. Effect of the Invention

[0034] In the lithium composite oxide according to the present invention, a certain relationship is maintained between the range of the full width at half maximum (FWHM) value of the (104) peak defined by a hexagonal lattice having an R-3m space group, the mole fraction of nickel, and the mass ratio of the first particles to the second particles, thereby preventing microcracks in the first particles and, as a result, improving the life characteristics of a battery including a nickel-rich positive electrode active material. [Brief description of the drawings]

[0035] [Figure 1] 1 is a SEM image of a lithium composite oxide according to an example of the present invention. [Diagram 2] 1 shows the results of particle size analysis of the mixture mass ratio of large particles and small particles of the lithium composite oxide according to an example of the present invention. [Diagram 3] 1 shows the results of particle size analysis of the mixture mass ratio of large particles and small particles of the lithium composite oxide according to an example of the present invention. [Figure 4] 1 is a graph comparing the characteristics of batteries having a bimodal structure with a single particle mixture and a bimodal structure with a multi-particle mixture. [Diagram 5] 1 is a graph comparing the characteristics of batteries having a bimodal structure with a single particle mixture and a bimodal structure with a multi-particle mixture. [Figure 6] 1 shows the results of XRD analysis of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 7] 1 shows the results of XRD analysis of a Si powder according to an embodiment of the present invention. [Figure 8]1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 9] 1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 10] 1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 11] 1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 12] 1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. [Figure 13] 1 is a graph comparing battery characteristics of lithium composite oxides according to examples of the present invention and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0036] The present invention will be described in detail below based on examples, but the present invention is not limited to the following examples.

[0037] <Measurement methods and terminology> During the XRD measurements, a Cu-Kα1 source was used as the X-ray source, and measurements were performed in the range of 10-70° (2θ) at 0.02° step intervals using the θ-2θ scan (Bragg-Brentano parafocusing geometry) method.

[0038] FWHM (104) and FWHM for Si powder (220) The measurements are calculated by Gaussian function fitting, and Gaussian function fitting for FWHM measurements can be performed using a variety of academic / public / commercial software well known to those skilled in the art.

[0039] The Si powder used was Si powder (product number 215619) manufactured by Sigma-Aldrich.

[0040] The mixed mass ratio of large particles to small particles was confirmed by particle size analysis as shown in FIG. 2 and FIG.

[0041] "FWHM range value" means FWHM (104) The term "optimum range of FWHM" means a value of -{0.04+(x-0.6)×0.25}, and "optimum range of FWHM" means that the FWHM value is -0.025 to 0.025.

[0042] "FWHM 大粒(104) " is the FWHM of large particles (104) FWHM 小粒(104) " is the FWHM of small particles (104) FWHM 混合(104) " is the FWHM of the lithium composite oxide produced by mixing large particles and small particles. (104) means the value.

[0043] <Production Example 1> A positive electrode active material having a molar fraction of large Ni particles of 0.80 and a positive electrode active material having a molar fraction of small Ni particles of 0.85 were produced by the following method.

[0044] Synthesis of large-grained positive electrode active material First, nickel sulfate, cobalt sulfate, and manganese sulfate were prepared and coprecipitation reaction was performed to synthesize a precursor. LiOH was added to the synthesized precursor, and the precursor was then calcined to produce a lithium composite oxide. Specifically, the precursor was mixed with LiOH, and then calcined in a calcination furnace to produce O 2 While maintaining the atmosphere, the temperature was increased at a rate of 1° C. / min, heat treatment was carried out for 10 hours, and then the mixture was naturally cooled to produce a positive electrode active material.

[0045] Next, distilled water was added to the lithium composite oxide, followed by washing with water for 1 hour. The washed lithium composite oxide was filtered and then dried to obtain large particles of a positive electrode active material having an average diameter of 11 to 13 μm.

[0046] Method for synthesizing small, single-particle positive electrode active material First, nickel sulfate, cobalt sulfate, and manganese sulfate were prepared and coprecipitation reaction was performed to synthesize a precursor. LiOH was added to the synthesized precursor, and the precursor was then calcined to produce a lithium composite oxide. Specifically, the precursor was mixed with LiOH, and then calcined in a calcination furnace to produce O 2 While maintaining the atmosphere, the temperature was increased at 1° C. / min, and heat treatment was performed at 900° C. for 10 hours, followed by natural cooling to produce a positive electrode active material.

[0047] Next, the lithium composite oxide was crushed into particles of 3 to 4 μm using a crusher, and then washed with distilled water for 1 hour. The washed lithium composite oxide was filtered and then dried to obtain a small-grain positive electrode active material, which is a single particle.

[0048] Mixing large and small particles to produce the final bimodal cathode active material Next, the large-particle positive electrode active material and the small-particle positive electrode active material, which are single particles, are mixed with a boron (B)-containing raw material (H 3 BO 3 ) and coated with B. 3 BO 3 ) was mixed in such a manner that the amount of the mixture was 0.2% by weight based on the total weight of the lithium composite oxide. 2 While maintaining the atmosphere, the temperature was raised at a rate of 2° C. / min, heat treatment was carried out for 5 hours, and then the mixture was naturally cooled to obtain a lithium composite oxide.

[0049] The lithium composite oxide thus produced was subjected to SEM measurement and is shown in FIG.

[0050] <Manufacturing example> Battery manufacturing The positive electrode active material for lithium secondary batteries produced in the Production Example, artificial graphite as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in a weight ratio of 85:10:5 to produce a slurry. The slurry was uniformly applied to an aluminum foil having a thickness of 15 μm, and vacuum dried at 135° C. to produce a positive electrode for lithium secondary batteries.

[0051] A coin battery was manufactured in a conventional manner using the positive electrode, a lithium foil as a counter electrode, a 20 μm-thick porous polypropylene membrane as a separator, and an electrolyte prepared by dissolving LiPF6 at a concentration of 1.15 M in a solvent containing ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:1:6.

[0052] <Experimental Example 1> FIG. 6 shows the XRD analysis results of Examples 1-1 to 1-4 and Comparative Examples 1-1 to 1-2 produced by the production method of Production Example 1 described above. All of the samples were hexagonal α-NaFeO 2 (R-3m space group) structure was confirmed.

[0053] Moreover, for FWHM correction, the results of analyzing Si powder using the same XRD equipment and conditions are shown in FIG.

[0054] Next, FWHM (104) The values ​​were measured and are shown in Tables 1 and 2. [Table 1] [Table 2]

[0055] By the manufacturing method of the above-mentioned Manufacturing Example 1, a lithium composite oxide having a molar fraction of large Ni particles of 0.80 and a molar fraction of small Ni particles of single particles of 0.85 was manufactured, and then the mass ratio of the large particles, the mass ratio of the small particles, and the FWHM due to the Ni molar fraction were calculated. 混合(104) The range of FWHM was calculated according to the relational expression of the present invention. Next, the batteries according to the above-mentioned manufacturing examples were manufactured, and the discharge capacity and life characteristics were measured. The results are shown in Table 3 below and in FIGS. [Table 3]

[0056] According to Table 3, FIGS. 8 and 9, it was confirmed that the battery discharge capacity and life were excellent in Examples 1-1 to 1-4, in which the FWHM range value satisfies the optimal FWHM range, whereas the battery discharge capacity and life were inferior in Comparative Examples 1-1 and 1-2, in which the FWHM range value did not satisfy the optimal FWHM range.

[0057] <Production Example 2> A positive electrode active material having a molar fraction of large Ni particles of 0.88 and a positive electrode active material having a molar fraction of small Ni particles of 0.88 were produced.

[0058] Synthesis of large multi-particle positive electrode active material First, nickel sulfate, cobalt sulfate, and manganese sulfate were prepared and coprecipitation reaction was performed to synthesize a precursor. LiOH was added to the synthesized precursor, and the precursor was then calcined to produce a lithium composite oxide. Specifically, the precursor was mixed with LiOH, and then calcined in a calcination furnace to produce O 2 While maintaining the atmosphere, the temperature was increased at 1° C. / min, heat treatment was performed for 10 hours, and then the mixture was naturally cooled to produce a positive electrode active material. Large particles of the positive electrode active material having an average diameter of 11 to 13 μm were produced.

[0059] Method for synthesizing small, single-particle positive electrode active material First, nickel sulfate, cobalt sulfate, and manganese sulfate were prepared and coprecipitation reaction was performed to synthesize a precursor. LiOH was added to the synthesized precursor, and the precursor was then calcined to produce a lithium composite oxide. Specifically, the precursor was mixed with LiOH, and then calcined in a calcination furnace to produce O 2 While maintaining the atmosphere, the temperature was increased at 1° C. / min, and heat treatment was performed at 900° C. for 10 hours, followed by natural cooling to produce a positive electrode active material.

[0060] Next, the lithium composite oxide was pulverized to a size of 3 to 4 μm using a pulverizer to obtain small single-particle positive electrode active material.

[0061] Mixing large and small particles to produce the final bimodal cathode active material Next, the large-particle positive electrode active material, which is a multiparticle, and the small-particle positive electrode active material, which is a single particle, are mixed with Al using a mixer. 2 O 3 and ZrO2 The mixture was mixed with Al and Zr and coated with O 2 While maintaining the atmosphere, the temperature was increased at a rate of 2° C. / min, heat treatment was carried out for 5 hours, and then the material was naturally cooled.

[0062] Next, distilled water was added to the lithium composite oxide, followed by washing with water for 1 hour, filtering, and then drying to obtain a lithium composite oxide.

[0063] <Experimental Example 2> As a result of XRD analysis of Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-2 manufactured by the manufacturing method of the above-mentioned Manufacturing Example 2, all of the samples had a hexagonal α-NaFeO 2 (R-3m space group) structure was confirmed.

[0064] Next, FWHM (104) The values ​​were measured and are shown in Tables 4 and 5. [Table 4] [Table 5]

[0065] By the manufacturing method of the above-mentioned Manufacturing Example 2, a lithium composite oxide having a molar fraction of large Ni particles of 0.88 and a molar fraction of small Ni particles of single particles of 0.88 was manufactured, and then the mass ratio of the large particles, the mass ratio of the small particles, and the FWHM due to the Ni molar fraction were calculated. 混合(104) The range of FWHM was calculated according to the relational expression of the present invention. Next, the batteries according to the above-mentioned manufacturing examples were manufactured, and the discharge capacity and life characteristics were measured. The results are shown in Table 6 below and in Figs. [Table 6]

[0066] According to Table 6, FIGS. 10 and 11, it was confirmed that the battery discharge capacity and life were excellent in Examples 2-1 to 2-4, in which the FWHM range value satisfies the optimal FWHM range, whereas the battery discharge capacity and life were inferior in Comparative Examples 2-1 and 2-2, in which the FWHM range value did not satisfy the optimal FWHM range.

[0067] <Production Example 3> A lithium composite oxide was produced in the same manner as in Production Example 2 above, except that the molar fraction of the large Ni particles, which were multiparticles, was 0.94, the molar fraction of the small Ni particles, which were single particles, was 0.92, and coating with Ti and Zr was performed.

[0068] <Experimental Example 3> As a result of XRD analysis of Examples 3-1 to 3-4 and Comparative Examples 3-1 to 3-2 produced by the production method of Production Example 3 described above, it was confirmed that all of the samples had a hexagonal α-NaFeO2 (R-3m space group) structure.

[0069] Next, FWHM (104) The values ​​were measured and are shown in Tables 7 and 8. [Table 7] [Table 8]

[0070] By the manufacturing method of the above-mentioned Manufacturing Example 3, a lithium composite oxide having a molar fraction of large Ni particles of 0.94 and a molar fraction of small Ni particles of single particles of 0.92 was manufactured, and then the mass ratio of the large particles, the mass ratio of the small particles, and the FWHM due to the Ni molar fraction were calculated. 混合(104) The range of FWHM was calculated according to the relational expression of the present invention. Next, the batteries according to the above-mentioned manufacturing examples were manufactured, and the discharge capacity and life characteristics were measured. The results are shown in Table 9 below and in Figs. [Table 9]

[0071] According to Table 9, FIGS. 12 and 13, it was confirmed that the battery discharge capacity and life were excellent in Examples 3-1 to 3-4, in which the FWHM range value satisfies the optimal FWHM range, whereas the battery discharge capacity and life were inferior in Comparative Examples 3-1 and 3-2, in which the FWHM range value did not satisfy the optimal FWHM range.

[0072] <Experimental Example 4> Comparison of bimodal properties of multi-particle mixture and bimodal properties of single particle mixture When manufacturing a bimodal positive electrode active material of a high-nickel NCM by mixing large and small particles in a multi-particle form, the BET is reduced, gas generation is suppressed, and storage characteristics are improved by using a mixture of small particles in a single particle form rather than small particles in a multi-particle form.

[0073] The gas generation rate and life characteristics when using a bimodal mixture of multiple particles and a bimodal mixture of single particles are compared, and are shown in Table 10, Figures 4 and 5.

[0074] From FIG. 4, it can be seen that in the case of a bimodal mixture of multiple particles, the volume change of the pouch cell due to gas generation when left at high temperature is more than twice as large as in the case of a bimodal mixture of single particles. [Table 10]

Claims

1. The mixture includes a first particle having n1 (n>40) aggregated primary particles and a second particle having n2 (n≦20) aggregated primary particles, Represented by the following [chemical formula 1], A lithium composite oxide, in which the range of the full width at half maximum (FWHM) (deg., 2θ) of a (104) peak in an XRD peak defined by a hexagonal lattice having an R-3m space group is represented by the following [Relation 1]. [Chemical formula 1] Li a Ni x Coco y Mn z M 1-x-y-z O 2 (In the formula, M is selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and 0.9≦a≦1.3, 0.6≦x≦1.0, 0.0≦y≦=0.4, 0.0≦z≦0.4, and 0.0≦1-x-y-z≦0.4.) [Relationship 1] -0.025≦FWHM (104) −{0.04+(x 第1の粒子 −0.6) × 0.25}≦0.025 (In the formula, FWHM (104) is expressed by the following [Relationship 2]. [Relationship 2] FWHM (104) = {(FWHM 化学式1のpowder(104) −0.1×mass ratio of second particles) / mass ratio of first particles}-FWHM Si powder(220) (In the formula, FWHM 化学式1のpowder(104) indicates the full width at half maximum (FWHM) of the (104) peak observed at about 44.5° (2θ) from the XRD measurement value of the lithium composite oxide. Also, FWHM Si powder(220) indicates the full width at half maximum (FWHM) of the (220) peak observed at about 47.3° (2θ) from the XRD measurement of the Si powder. Also, x 第1の粒子 = (x - x 第2の粒子 * Mass ratio of the second particles) / mass ratio of the first particles, 第2の粒子 means the Ni molar ratio of the second particle The mass ratio means the ratio of the mass of the first particles to the total mass of the second particles.

2. 2. The lithium composite oxide according to claim 1, wherein the first particles have an average particle size of 8 to 20 μm.

3. 2. The lithium composite oxide according to claim 1, wherein the second particles have an average particle size of 0.1 to 7 μm.

4. The crystal structure of the lithium composite oxide is hexagonal α-NaFeO 2 The lithium composite oxide according to claim 1,

5. When the nickel content x is 0.97 to 0.99, the FWHM (104) The lithium composite oxide according to claim 1, wherein the range satisfies 0.108° (2θ) to 0.162° (2θ).

6. When the nickel content x is 0.93 to 0.95, the FWHM (104) The lithium composite oxide according to claim 1, wherein the range of is 0.098° (2θ) to 0.152° (2θ).

7. When the nickel content x is 0.87 to 0.89, the FWHM (104) The lithium composite oxide according to claim 1, wherein the range of is 0.083° (2θ) to 0.137° (2θ).

8. When the nickel content x is 0.79 to 0.81, the FWHM (104) The lithium composite oxide according to claim 1, wherein the range of is 0.063° (2θ) to 0.117° (2θ).

9. A method for producing the lithium composite oxide according to claim 1, a first step of synthesizing a first positive electrode active material precursor including first particles in which n1 (n>40) primary particles are aggregated, adding a lithium compound thereto, and then calcining the resulting mixture to produce a first positive electrode active material; a second step of synthesizing a second positive electrode active material precursor including second particles in which primary particles are aggregated to n2 (n2≦20), adding a lithium compound thereto, and then calcining the resulting mixture; a third step of grinding the material formed in the second step to produce a second positive electrode active material; a fourth step of mixing the first positive electrode active material with a second positive electrode active material; and a fifth step of coating or doping the mixed material with material M followed by a heat treatment; The method for producing a lithium composite oxide includes the steps of:

10. 10. The method for producing a lithium composite oxide according to claim 9, wherein the lithium compound added in the first step or the second step is LiOH.

11. 10. The method for producing a lithium composite oxide according to claim 9, wherein the first positive electrode active material produced in the first step has an average particle size of 8 to 20 μm.

12. 10. The method for producing a lithium composite oxide according to claim 9, wherein the second positive electrode active material produced in the third step has an average particle size of 0.1 to 7 μm.

13. The method for producing a lithium composite oxide according to claim 9, further comprising a step of washing with water after the firing in the first step, after the firing in the second step, or after the pulverization in the third step.

14. The method for producing a lithium composite oxide according to claim 9 , further comprising a step of washing with water after the heat treatment in the fifth step.

15. 10. The method for producing a lithium composite oxide according to claim 9, wherein in the fifth step, the substance M is selected from the group consisting of B, Ba, Ce, Cr, F, Mg, Al, Cr, V, Ti, Fe, Zr, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof.

Citation Information

Patent Citations

  • Cathode active material, method of producing the same, and cathode and lithium secondary battery employing the same

    JP2015018803A

  • Lithium ion battery positive electrode material and lithium ion battery

    JP2019021627A

  • Positive electrode active material composition for lithium secondary battery and lithium secondary battery including the same

    JP2019091691A

  • Industrial furnace and combustion control method for industrial furnace

    KR1020200059128A

  • Non-aqueous electrolyte secondary battery

    WO2019187538A1